129k views
2 votes
By what number should you multiply the first equation to solve using elimination?

–3x – 2y = 2
–9x + 3y = 24

–3
6
–9
3

User Fateddy
by
5.7k points

1 Answer

4 votes

Answer:

3

Explanation:

We would be eliminating -9x from the equations.

Thus, we need to make the (-3x) into (-9x) in the first equation.

-9x ÷ -3x = 3

After that, you should be able to solve the equations:

-3x - 2y = 2

Equation 1×3: -9x - 6y = 6

-9x + 3y = 24

User DaTebe
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.